2015
DOI: 10.1007/s10862-015-9500-3
|View full text |Cite
|
Sign up to set email alerts
|

The Co-Development of Parenting Stress and Childhood Internalizing and Externalizing Problems

Abstract: Although the detrimental influence of parenting stress on child problem behavior is well established, it remains unknown how these constructs affect each other over time. In accordance with a transactional model, this study investigates how the development of internalizing and externalizing problems is related to the development of parenting stress in children aged 4–9. Mothers of 1582 children participated in three one-year interval data waves. Internalizing and externalizing problems as well as parenting str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
107
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(144 citation statements)
references
References 65 publications
(79 reference statements)
20
107
3
4
Order By: Relevance
“…As expected, child mania and anxiety symptoms, and presence of any disruptive behavior disorder, were associated with increased caregiver stress (e.g., Anderson, 2008; Bussing et al 2003a; Bussing et al, 2003b; Deater-Deckard, 2004; Stone et al, 2016; Vaughan et al, 2013). These problem areas likely exacerbate parenting stress in different ways.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…As expected, child mania and anxiety symptoms, and presence of any disruptive behavior disorder, were associated with increased caregiver stress (e.g., Anderson, 2008; Bussing et al 2003a; Bussing et al, 2003b; Deater-Deckard, 2004; Stone et al, 2016; Vaughan et al, 2013). These problem areas likely exacerbate parenting stress in different ways.…”
Section: Discussionsupporting
confidence: 72%
“…While the relationship between parenting stress and childhood psychopathology appears to be transactional (Mackler et al, 2015; Stone, Mares, Otten, Engels, & Janssens, 2016), and thus the directionality of effects is not well understood, several predictors of caregiver burden have been identified, including: children’s symptom severity, functional impairment, and type of mental illness; and parents’ age, race/ethnicity, psychiatric history, and perceived amount of social support (Mendenhall & Mount, 2011). Specifically, parenting stress is more pronounced if caregivers are older (Schoeder & Remer, 2007), Caucasian (McCabe, Yeh, Lau, Garland, & Hough, 2003), psychiatrically impaired (Angold et al, 1998), with attention-deficit/hyperactivity disorder (ADHD) symptoms (Algorta et al, 2014; Wiener, Biondic, Grimbos, & Herbert, 2016), depressive symptoms (Theule, Wiener, Tannock, & Jenkins, 2013), or lower perceived social support (Schoeder & Remer, 2007).…”
Section: Parenting Stress Among Caregivers Of Children With Psychiatrmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little known about whether mothers' mental health could be affected by the stress of having children with behavioural and mental health problems. Studies have reported a reciprocal association between maternal stress and child externalising behaviours (Stone et al, 2016) as well as an association between psychopathology in daughters and long-term depression experienced by mothers (Sellers et al, 2016). The possibility of a reverse causal pathway between child and adolescent behaviour problems and women's mental health impairment over time will be investigated.…”
Section: Offspring Behaviours and Women's Mental Health Over Timementioning
confidence: 99%
“…They suggested that child behaviour affected parenting behaviour and visa-versa, with children's conduct problems being associated with decreased parental warmth and harsher parenting (Hipwell et al, 2008). Reciprocity between children's externalizing behaviours and parenting stress has been also found (Stone et al, 2016). While family stress has been identified as an environmental risk factor associated with youth psychopathology (Hammen et al, 2004), it is possible that child behaviour problems also contribute to stress levels within the family.…”
Section: Impact On Familiesmentioning
confidence: 99%